Two new species of Buenoa (Hemiptera: Heteroptera: Notonectidae) from Colombia, with a key to the species in Colombia - Padilla-Gil, Dora N. (Zootaxa, 2012)
Buenoa penta sp. n. and Buenoa analoga sp. n., are described from Tumaco municipality on the Pacific coast of the Department of Nariño. A key to species of Buenoa in Colombia is given.